"In these streets": the saliency of place in an alternative black mental health resource centre. Issue 1 (27th November 2019) - Wainwright, John; McKeown, Mick; Kinney, Malcolm
Abstract : Purpose: The purpose of this paper is to explore experiences of survivors of the mental health system regularly attending a mental health resource centre predominantly but not exclusively focussed on needs of the BAME community. Design/methodology/approach: In total, 25 participants took part in a qualitative research study regarding their experiences of mental health and racism, alternative mental health support and struggles in the local black community. Findings: Issues of race, place and space were central to the experiences of BAME mental health survivors. Participants emphasised the importance of place-based support in their everyday life, with the service provided engendering a sense of belonging conducive to coping with various struggles. Race and racism were also central to these daily struggles and the place of Liverpool 8 was at the core of notions of identity and belonging. The space within the centre provided a sanctuary from the combined discriminations and exclusions attendant on being BAME survivors of the mental health system. Practical implications: Attention to matters of place and space appears crucial to the articulation of appropriate support. Social implications: Place is salient to understanding the intersecting identities/experience of racism and mental health discrimination, constituting the basis for a concept of placism; associated with exclusions from feeling safe and included in everyday public places (including within the black community) with the exception of the welcoming and unconditionally accepting space of the centre. Originality/value: This paper is the first to inquire into place-based experiences of alternative black mental health support. Placism is a novel construct that merits further inquiry and theoretical development.